Generalised fleet maintenance modelling - Reyes Campaña, Héctor Rodrigo (2019)
In the new global economy, asset management has become a central issue for the defence industry. It is well known that countries try to maintain the peace and security of their borders by investing in the weapon systems of their armed forces. Unfortunately, owning, managing, and maintaining a powerful fleet of defence vehicles in normal condition to work is extremely expensive. Although defence budgets remain a priority in almost all countries, during the last decade, budgets in this sector have continuously decreased. For example, budgets for military defence in South America have been severely affected by different external and internal economic factors, such as natural disasters and fluctuations in the raw materials price in the international market. In fact, maintaining the condition of a defence fleet on a low budget is a challenge for the armed forces of South American and developing countries.